The impact of changes in regulations on Malaysian IPOs. Issue 3 (30th July 2021) - Mohd-Rashid, Rasidah; Tajuddin, Ahmad Hakimi; Khaw, Karren Lee-Hwei; Ong, Chui Zi
Abstract : Purpose: This study aims to examine the changes in equity guidelines and initial returns in the Malaysian initial public offering (IPO) market. Design/methodology/approach: The study uses cross-sectional data over 16 years from 2000 to 2016. It uses ordinary least squares for the baseline model and incorporates an interaction term, quantile regression, quadratic term, break test and logit regression model for further analysis. Findings: The results support the propositions that lockup provisions signal commitment and demand increase initial returns. The revision in the Bumiputera equity requirement means that issuers no longer need to discount offer prices to entice investors. Finally, the revised Sharīʿah-compliance screening requirement ensures that stocks are better in quality and more transparent, leading to a higher demand that drives prices upwards. Research limitations/implications: This study's findings provide insights into how issuers can secure good subscriptions. Besides, policymakers should ensure that firms disclose the required information in their prospectuses. Originality/value: This study adds to the body of knowledge on whether and how the regulatory requirements affect IPO initial returns.